A fast self-cleaning SERS-active substrate based on an inorganic–organic hybrid nanobelt film1. Issue 32 (28th August 2015) - Hao, Rui; Lin, Jie; Wang, Hua; Li, Bo; Li, Fengshi; Guo, Lin
<x xml:space="preserve">Abstract</x> Ag@Ag(DMSO)xCl nanobelts can achieve fast self-cleaning by the photodegradation of probe molecules during the in situ SERS detection process.